Experimental poisoning by Crotalaria pallida (mucronata) in sheep Intoxicação experimental por folhas de Crotalaria pallida (mucronata) em ovinos - Borelli V.* (2016)
This paper describes the toxic potential of the green leaves of Crotalaria pallida and the clinical signs in experimentally poisoned sheep. Green leaves of C. pallida were collected in São João do Sul, Santa Catarina, and administered orally to six adult sheep, as single dose of 40, 20, 10, 5, 2.5 and 2.5g/kg, and for two sheep at doses of 0.63 and 1.25g/kg during 30 days. The poisoning was reproduced at lethal doses of 2.5g/kg. One of the sheep that received a single dose of 2.5g/kg and another that received daily doses did become ill. All sheep wich developed clinical signs died between 13 and 22 hours after administration of the plant. Slight signs started in about 11 hours after ingestion of the plant, and clinical signs included loose stool, restlessness and increased heart and respiratory rates. A few minutes preceding death, pronounced abdominal breathing and severe dyspnea was observed. The main gross lesions were restricted to the thoracic cavity, as severe pulmonary edema and hydrothorax. Lung microscopy showed marked edema in the diffuse pleural surface, the interlobular spaces and around the peribronchial arteries. Multifocal edema was observed within alveoli and around the bronchi and bronchioles, and mild multifocal infiltration of neutrophils. The clinical and pathological alerations of the experimental poisoning was similar to that observed in the spontaneous poisoning, characterized by marked pulmonary edema and death shortly after the onset of clinical signs.